Improving teachers’ understanding of reproductive health and sexuality education in special schools - Tati Hernawati; Tarishah Aulia; Wina Tri Saptari; Arif Prawira; Zulfa Rahmah Effendi; Prinanda Gustarin Ridwan; Euis Heryati; Agus Irawan Sensus; Imas Diana Aprilia; Fitri Mulyani (Himpunan Pengembang Kurikulum Indonesia, 2024)
The inability to achieve complete independence in students with special needs has the potential to make this group vulnerable to problems, including reproductive health and sexuality problems. These problems are suspected to be due to the lack of understanding and perception of teachers in the concept and implementation of reproductive health and sexuality education in Special Schools (SLB). This study was conducted to see teachers' understanding of reproductive health and sexuality education for students with special needs. Using a quantitative approach with a one-group pretest-posttest design, this study involved 15 teachers from six SLBs in Bandung City who were selected using the purposive sampling method. The data obtained were analyzed using the Wilcoxon Signed-Rank Test. The results of the study showed a significant increase in the average score, indicating that the efforts made could improve teachers' understanding of reproductive health and sexuality education. Teachers felt more prepared to deal with the problems of students with special needs regarding reproductive health and sexuality after participating in competency refresher courses by participating in training or discussions. Training and discussions that are planned systematically, sustainably, and comprehensively can improve teacher competence and, more broadly, can improve the quality of reproductive health and sexuality education in SLB. Abstrak Ketidakmampuan pencapaian kemandirian secara utuh pada peserta didik berkebutuhan khusus berpotensi membuat kelompok ini rentan terhadap masalah, termasuk masalah kesehatan reproduksi dan seksualitas. Permasalahan tersebut disinyalir karena adanya kekurangpahaman dan persepsi guru dalam tataran konsep dan implementasi pendidikan kesehatan reproduksi dan seksualitas di Sekolah Luar Biasa (SLB). Penelitian ini dilakukan untuk melihat pemahaman guru terhadap pendidikan kesehatan reproduksi dan seksualitas untuk peserta didik berkebutuhan khusus. Menggunakan pendekatan kuantitatif dengan one group pretest -posttest design, penelitian ini melibatkan 15 guru dari enam SLB di Kota Bandung yang dipilih dengan metode purposive sampling. Data yang diperoleh dianalisis dengan uji Wilcoxon Signed-Rank Test. Hasil penelitian menunjukan peningkatan rata-rata skor secara signifikan yang menunjukkan bahwa upaya yang dilakukan dapat meningkatkan pemahaman guru terhadap pendidikan kesehatan reproduksi dan seksualitas. Guru merasa lebih siap untuk menghadapi permasalahan peserta didik berkebutuhan khusus mengenai kesehatan reproduksi dan seksualitas setelah mengikuti penyegaran kompetensi dengan mengikuti pelatihan atau diskusi. Pelatihan dan diskusi yang direncanakan dengan sistematis, berkelanjutan, dan komprehensif dapat meningkatkan kompetensi guru dan secara lebih luas dapat meningkatkan kualitas pendidikan kesehatan reproduksi dan seksualitas di SLB.